2015
DOI: 10.1097/prs.0000000000001060
|View full text |Cite
|
Sign up to set email alerts
|

Cadaveric Study of Breast Measurements during Augmentation with Implants

Abstract: Implant shape, volume, and pocket location influence projection, causing it to increase in a linear fashion. Partial pectoralis major release seems to affect projection only for small volumes, but does not influence nipple position in the immediate setting. As projection increases with augmentation volume, cephalad movement of the nipple is produced by a relative increase in nipple-to-inframammary fold distance compared with the midclavicular point-to-nipple distance in our cadaveric sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, this study provided no insight into long-term outcomes observed in real patients, and the skin flaps have in preserving implant position. 10 Dorfman et al investigated geometric changes in breast projection and nipple positioning following NSM and subpectoral reconstruction with round or anatomical implants. 7 Although this study demonstrated that shaped implants had less nipple deviation from the point of maximal breast projection relative to round implants, it remains limited by the mean follow-up of 202 days and dynamic contribution of the pectoralis contraction.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study provided no insight into long-term outcomes observed in real patients, and the skin flaps have in preserving implant position. 10 Dorfman et al investigated geometric changes in breast projection and nipple positioning following NSM and subpectoral reconstruction with round or anatomical implants. 7 Although this study demonstrated that shaped implants had less nipple deviation from the point of maximal breast projection relative to round implants, it remains limited by the mean follow-up of 202 days and dynamic contribution of the pectoralis contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Several different systems have been applied to measuring breast morphometry to describe both the unoperated and operated breast and the differences between the two. These include simple tape measure-based systems, [11][12][13][14] measurements taken from standardized photographic images, 1,[15][16][17] and measurements taken from threedimensional scanning systems. [18][19][20][21][22] Although it has been suggested that tape measurements lead to considerable interobserver and intraobserver error, this is not the experience of the author.…”
Section: Discussionmentioning
confidence: 99%
“…Although discussions on the aesthetic outcomes and distinguishability of implant shapes in cis women have been long and ongoing, a recent anthropometric study showed that round and anatomically shaped implants influence breast morphology differently [7,17,24,26]. A cadaver study showed that anatomically shaped implants were more adept at creating a longer IMF-N, and to a lesser extent, lengthening the SN-N too [14]. Importantly, these outcomes reflected the morphology directly after implant placement and do not reflect long-term outcomes that tissue quality and implant texture might have on eventual breast shape and position.…”
Section: Discussionmentioning
confidence: 99%